A coating material and a preparation method thereof and a brake pad
By coating the surface of the brake pad friction block with potassium titanate and alumina, the Koch snowflake pattern is formed, which solves the problem of insufficient braking force and noise in the initial running-in stage of the brake pad, achieving higher friction coefficient and lower noise, extending service life and improving driving comfort.
Patent Information
- Application Number
- CN202411939052.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
AI Technical Summary
The braking force of the car brake pads during the initial running-in stage is low and accompanied by noise, which affects the comfort of the braking process, especially in pure electric vehicles of new energy vehicles.
Provided is a coating material, containing 40-70% potassium titanate and alumina, 8-12% liquid phenolic resin, 10-25% calcium carbonate, 1-5% sodium silicate, and 8-20% iron powder. The coating material is coated on the surface of the brake pad friction block to form a Koch snowflake pattern.
It effectively improves the friction coefficient and surface smoothness of the brake pads, reduces braking noise, extends the service life of the brake pads, and improves driving comfort.
Smart Images

Figure CN119775807A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobiles, and in particular to a coating material and a preparation method thereof, and a brake pad. Background Art
[0002] Brake pads are extremely important components in the automobile braking system. The braking process of a car uses the friction between the brake pads and the brake disc to generate friction to slow down or stop the vehicle. During the initial running-in stage of the installation of the brake pads, the initial braking force is low due to insufficient contact between the brake pads and the brake disc surface, and accompanied by noise, which affects the comfort of the braking process. Especially for new energy vehicles and pure electric vehicles, since there is no engine, they are more sensitive to braking noise. Summary of the invention
[0003] In view of the above problems existing in the prior art, the present invention provides a coating material and a preparation method thereof and a brake pad to improve the problem of noise generated during the initial braking process of a car and the problem of insufficient initial braking performance.
[0004] To achieve the above-mentioned purpose and other related purposes, the first aspect of the present invention provides a coating material, which comprises the following components, measured by mass percentage, of potassium titanate and aluminum oxide: 40-70%, liquid phenolic resin 8-12%, calcium carbonate 10-25%, sodium silicate 1-5%, and iron powder 8-20%, wherein the mass ratio of the potassium titanate to the aluminum oxide is (25-40):(15-30).
[0005] In one embodiment of the present invention, the gel time of the liquid phenolic resin is 120-180s / 150°C.
[0006] In one embodiment of the present invention, the particle size of the potassium titanate is 20-50 μm.
[0007] In one embodiment of the present invention, the particle size of the aluminum oxide is 3-7 μm.
[0008] A second aspect of the present invention provides a method for preparing a coating material, comprising the following steps:
[0009] Adding potassium titanate, aluminum oxide, calcium carbonate, sodium silicate and iron powder into liquid phenolic resin;
[0010] In a vacuum mixer, the mixture is first stirred at a speed of 80 to 150 r / min for 3 to 5 min, and then stirred at a speed of 200 to 300 r / min for 3 to 5 min to obtain a coating material.
[0011] A third aspect of the present invention provides a brake pad, comprising a steel back, a friction block and a coating made of the above coating material, wherein the coating is coated on the surface of the friction block.
[0012] In one embodiment of the present invention, the coating area of the coating is 50-70% of the area of the friction block.
[0013] In one embodiment of the present invention, the pattern of the coating is a Koch snowflake pattern.
[0014] In one embodiment of the present invention, the preparation of the coating comprises the following steps:
[0015] Applying the coating material to the surface of the friction block;
[0016] The coating material is cured at 150° C. for 120 to 180 seconds to form the coating.
[0017] In one embodiment of the present invention, the coating material has a coating thickness of 0.1-0.3 mm.
[0018] The coating material provided by the present invention uses potassium titanate and aluminum oxide as main raw materials. Potassium titanate has good wear resistance and high temperature resistance, can effectively extend the service life of brake pads, and can still maintain stable performance at high temperatures. Aluminum oxide not only has good wear resistance, but also can improve the surface smoothness of brake pads, reduce braking noise, and improve driving comfort. Calcium titanate and iron powder can both increase the friction coefficient of brake pads. Furthermore, the coating material is coated on the friction block in a Koch snowflake pattern, which can effectively save the use of coating materials, and the Koch snowflake pattern tends to an infinite circumference, which can effectively dissipate the heat generated by the contact friction between the coating material and the brake disc, avoiding the generation of local heat accumulation areas on the friction surface and affecting the stability of the braking performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0020] Figure 1 is a flow chart of the preparation of the coating material of the present invention in one embodiment;
[0021] Figure 2 It is a schematic structural diagram of a brake pad of the present invention in one embodiment;
[0022] Figure 3 A schematic diagram of the surface of a brake pad according to an embodiment of the present invention;
[0023] Figure 4FIG. 1 is a flow chart of the preparation of a coating of a brake pad in one embodiment of the present invention.
[0024] Component number description:
[0025] 1. Steel back; 2. Friction block; 3. Coating. DETAILED DESCRIPTION
[0026] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0027] When numerical ranges are given in the embodiments, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any method, device and material of the prior art similar or equivalent to the method, device and material in the embodiments of the present invention can also be used to implement the present invention.
[0028] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" etc. used in this specification are only for the convenience of description and are not intended to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships, without substantially changing the technical content, should also be regarded as the scope of implementation of the present invention.
[0029] The present invention provides a coating material, characterized in that, measured by mass percentage of the friction block, the friction block comprises the following components: 40-70% potassium titanate and aluminum oxide, 8-12% liquid phenolic resin, 10-25% calcium carbonate, 1-5% sodium silicate, and 8-20% iron powder, wherein the mass ratio of potassium titanate to aluminum oxide is (25-40):(15-30).
[0030] In the present invention, the components of the coating material function as follows:
[0031] Liquid phenolic resin: As an adhesive, it has good wettability and mixing uniformity, and can form good adhesion with the surfaces of various substrates. Adding liquid phenolic resin to the coating can significantly improve the adhesion of the coating to the substrate, making the coating more firmly attached to the surface of the substrate and not easy to peel off.
[0032] Potassium titanate: Potassium titanate has good wear resistance and high temperature resistance. As a ceramic material, potassium titanate has suitable hardness and high wear resistance, which can effectively extend the service life of the coating material, and can still maintain stable performance at high temperatures, and will not fail due to high temperature. Stable friction performance: As a material with a mild friction coefficient, the addition of potassium titanate can effectively prevent the high friction of aluminum oxide from damaging the brake disc and reduce the generation of braking noise. Alumina: Alumina is a material with high hardness and high wear resistance. It can not only effectively increase the friction coefficient and improve the initial friction characteristics between the brake pad and the brake disc, but also has good thermal conductivity and thermal stability. It can effectively conduct and dissipate the heat generated by the friction of the brake disc, making the friction coefficient higher, more stable and more durable. It can also improve the surface smoothness of the brake pad, extend the life of the coating material, and reduce the noise and vibration generated during braking.
[0033] Calcium carbonate: As a filler, calcium carbonate can improve the thermal stability of the friction block and the thermal decay performance of the material.
[0034] Sodium silicate: Sodium silicate can not only be used as a dispersant to improve the dispersibility of powder and ensure the uniformity of the material, but also as a high-temperature binder to bond different materials together and improve the overall strength and wear resistance of the brake pad.
[0035] Iron powder: It can adjust the friction performance and keep the friction coefficient stable. The porous structure of iron powder is beneficial to reduce the braking noise of brake pads during use.
[0036] In one embodiment, the gel time of the liquid phenolic resin is 120-180s / 150°C. For example, at 150°C, the gel time of the liquid phenolic resin is any value within the range of 120s, 140s, 150s, 180s, etc., within the range of 120-180s.
[0037] In one embodiment, the particle size of potassium titanate is 20-50 μm, for example, any value between 20 μm, 30 μm, 40 μm or 50 μm.
[0038] In one embodiment, the particle size of aluminum oxide is 3-7 μm, for example, any value between 3 μm, 4 μm, 5 μm, 6 μm or 7 μm.
[0039] See also Figure 1The present invention also provides a method for preparing a coating material, comprising the following steps:
[0040] S11, adding potassium titanate, aluminum oxide, calcium carbonate, sodium silicate and iron powder into liquid phenolic resin;
[0041] S12. In a vacuum mixer, first stir at a speed of 80 to 150 r / min for 3 to 5 min, and then stir at a speed of 200 to 300 r / min for 3 to 5 min to obtain a coating material.
[0042] In step S1, the coating material includes the following components, measured in percentage by mass: 40-70% potassium titanate and aluminum oxide, 8-12% liquid phenolic resin, 10-25% calcium carbonate, 1-5% sodium silicate, and 8-20% iron powder, wherein the mass ratio of the potassium titanate to the aluminum oxide is (25-40):(15-30).
[0043] In step S2, the coating material is first stirred at a lower speed for the first time, so that the powder can be gradually infiltrated and preliminarily dispersed in the liquid phenolic resin; and then stirred at a higher speed for the second time so that the coating material can be mixed more evenly and dispersed better, ensuring that the powder is fully in contact with the liquid phenolic resin. Exemplarily, the speed of the first stirring can be any value in 80 to 150 r / min such as 80r / min, 100r / min, 130r / min or 150r / min, and the time of the first stirring can be 3 to 5min, such as any value in 3 to 5min such as 3min, 4min or 5min; the speed of the second stirring can be any value in 200 to 300r / min such as 200r / min, 230r / min, 260r / min or 300r / min.
[0044] See also Figure 2 The present invention also provides a brake pad, which includes a steel back, a friction block and a coating made of the above coating material, and the coating is coated on the surface of the friction block. In the brake pad of the present application, the friction block is fixed to the steel back by high-temperature pressing and bonding, and the specific fixing method is performed according to the bonding method commonly used in the art.
[0045] In one embodiment, the thickness of the coating is 0.1-0.3 mm, for example, 0.1 mm, 0.2 mm, 0.3 mm, or any other value within the range of 0.1-0.3 mm.
[0046] In one embodiment, the coating area of the coating is 50% to 70% of the area of the friction block, such as 50%, 60% or 70%, or any value within the range of 50% to 70%.
[0047] See also Figure 3In the early stage of brake pad installation, the surfaces of the brake pad and the brake disc cannot be completely fitted together. It takes a period of running-in before the contact surface can achieve an ideal contact effect, thereby achieving a stable braking effect. This results in partial contact of the disc in the early stage of brake pad installation, resulting in a weak and unstable braking torque of the vehicle. Local contact will cause a higher temperature in the contact area, which can easily lead to hot spots on the brake disc and metal pick up (MPU) problems, thereby damaging the brake disc. Therefore, in one embodiment, the pattern of the coating is a Koch snowflake pattern. The Koch snowflake pattern effectively utilizes the characteristics of the Koch curve, that is, within a limited area, the circumference tends to infinity. The limited area can effectively save the use of materials, and the circumference tending to infinity can effectively dissipate the heat generated by the contact friction between the coating material and the brake disc, avoiding the generation of local heat accumulation areas on the friction surface and affecting the stability of the braking performance.
[0048] See also Figure 4 In one embodiment, the preparation of the coating comprises the following steps:
[0049] S21, applying the coating material on the surface of the friction block;
[0050] S22, curing the coating material at 150°C for 120 to 180 seconds to form a coating.
[0051] In step S21, the coating material may be coated on the surface of the friction block by conventional technical means in the art, such as a roller brush or a screen with Koch curve pattern characteristics.
[0052] In step S22, the curing time of the friction block may be any value within the range of 120 to 180 seconds, such as 120 seconds, 140 seconds, 160 seconds or 180 seconds.
[0053] The technical scheme of the present invention is described in detail below through several specific examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.
[0054] Example 1
[0055] The preparation method of the brake pad in this embodiment is as follows: the coating material is weighed in the proportion of 30% potassium titanate, 25% aluminum oxide, 15% calcium carbonate, 5% sodium silicate, 15% iron powder and 10% liquid phenolic resin in terms of mass percentage of the coating material; the liquid phenolic resin is placed in a vacuum mixer, and then potassium titanate, aluminum oxide, calcium carbonate, sodium silicate and iron powder are added to the liquid phenolic resin, and the mixture is stirred by the vacuum mixer, and the mixture is stirred at a speed of 80 r / min for 3 minutes, and then at a speed of 200 r / min for 3 minutes to obtain the coating material. The coating material is evenly applied to the surface of the friction block with a roller brush having a Kohler curve characteristic pattern, and the brake pad is baked at 150° C. for 140 seconds to obtain a brake pad with a coating on the surface.
[0056] In this embodiment, the diameter of potassium titanate is 30 μm, the diameter of aluminum oxide is 5 μm, the gel time of liquid phenolic resin at 150° C. is 140 s, the coating area is 60% of the friction block area, and the coating thickness of the coating material is 0.25 mm.
[0057] Example 2
[0058] The preparation method of the brake pad in this embodiment is as follows: the coating material is weighed in the proportion of 40% potassium titanate, 15% aluminum oxide, 20% calcium carbonate, 3% sodium silicate, 10% iron powder and 12% liquid phenolic resin in terms of mass percentage of the coating material; the liquid phenolic resin is placed in a vacuum mixer, and then potassium titanate, aluminum oxide, calcium carbonate, sodium silicate and iron powder are added to the liquid phenolic resin, and the mixture is stirred by the vacuum mixer, and the stirring is performed at a speed of 100 r / min for 5 minutes, and then at a speed of 300 r / min for 5 minutes to obtain the coating material. The coating material is evenly applied to the surface of the friction block with a roller brush having a Kohler curve characteristic pattern, and the brake pad is baked at 150°C for 160 seconds to obtain a brake pad with a coating on the surface.
[0059] In this embodiment, the diameter of potassium titanate is 50 μm, the diameter of aluminum oxide is 5 μm, the gel time of liquid phenolic resin at 150° C. is 160 s, the coating area is 70% of the friction block area, and the coating thickness of the coating material is 0.1 mm.
[0060] Example 3
[0061] The preparation method of the brake pad in this embodiment is as follows: the coating material is weighed in the proportion of 25% potassium titanate, 15% aluminum oxide, 25% calcium carbonate, 4% sodium silicate, 20% iron powder and 11% liquid phenolic resin in terms of mass percentage of the coating material; the liquid phenolic resin is placed in a vacuum mixer, and then potassium titanate, aluminum oxide, calcium carbonate, sodium silicate and iron powder are added to the liquid phenolic resin, and the mixture is stirred by the vacuum mixer, and the mixture is stirred at a speed of 150 r / min for 4 minutes, and then at a speed of 230 r / min for 4 minutes to obtain the coating material. The coating material is evenly applied to the surface of the friction block with a roller brush having a Kohler curve characteristic pattern, and the brake pad is baked at 150° C. for 180 seconds to obtain a brake pad with a coating on the surface.
[0062] In this embodiment, the diameter of potassium titanate is 20 μm, the diameter of aluminum oxide is 7 μm, the gel time of liquid phenolic resin at 150° C. is 180 s, the coating area is 50% of the friction block area, and the coating thickness of the coating material is 0.3 mm.
[0063] Example 4
[0064] The preparation method of the brake pad in this embodiment is as follows: the coating material is weighed in the proportion of 40% potassium titanate, 30% aluminum oxide, 10% calcium carbonate, 2% sodium silicate, 10% iron powder and 8% liquid phenolic resin in terms of mass percentage of the coating material; the liquid phenolic resin is placed in a vacuum mixer, and then potassium titanate, aluminum oxide, calcium carbonate, sodium silicate and iron powder are added to the liquid phenolic resin, and the mixture is stirred by the vacuum mixer, and the mixture is stirred at a speed of 130 r / min for 4 minutes, and then at a speed of 270 r / min for 3 minutes to obtain the coating material. The coating material is evenly applied to the surface of the friction block with a roller brush having a Kohler curve characteristic pattern, and the brake pad is baked at 150° C. for 120 seconds to obtain a brake pad with a coating on the surface.
[0065] In this embodiment, the diameter of potassium titanate is 40 μm, the diameter of aluminum oxide is 3 μm, the gel time of liquid phenolic resin at 150° C. is 120 s, the coating area is 55% of the friction block area, and the coating thickness of the coating material is 0.2 mm.
[0066] Example 5
[0067] The preparation method of the brake pad in this embodiment is as follows: the coating material is weighed in the proportion of 33% potassium titanate, 30% aluminum oxide, 18% calcium carbonate, 1% sodium silicate, 8% iron powder, and 10% liquid phenolic resin in terms of mass percentage of the coating material; the liquid phenolic resin is placed in a vacuum mixer, and then potassium titanate, aluminum oxide, calcium carbonate, sodium silicate and iron powder are added to the liquid phenolic resin, and the mixture is stirred by the vacuum mixer, and the mixture is stirred at a speed of 90 r / min for 5 minutes, and then at a speed of 260 r / min for 4 minutes to obtain the coating material. The coating material is evenly applied to the surface of the friction block with a roller brush having a Kohler curve characteristic pattern, and the brake pad is baked at 150° C. for 150 seconds to obtain a brake pad with a coating on the surface.
[0068] In this embodiment, the diameter of potassium titanate is 35 μm, the diameter of aluminum oxide is 4 μm, the gel time of liquid phenolic resin at 150° C. is 150 s, the coating area is 65% of the friction block area, and the coating thickness of the coating material is 0.25 mm.
[0069] Comparative Example
[0070] In the present application, a brake pad not coated with a coating material is used as a comparative example.
[0071] The friction coefficient and noise performance test were conducted on the brake pads in Examples 1 to 5 and the comparative example. The friction coefficient test standard was conducted according to the SAE J2522-2014 standard of the American Society of Automotive Engineers, and the noise performance test standard was conducted according to the SAE J2521-2013 standard of the American Society of Automotive Engineers. SAE J2522-2014 and SAE J2521-2013 are the friction coefficient and noise test standards with high recognition in the brake pad industry. The Greening and Burnish chapters in the SAE J2522-2014 standard are mainly used to evaluate the friction coefficient of the new brake pad in the initial and running-in stages after installation. The SAE J2521-2013 standard evaluates the noise performance of the brake pad by collecting the noise during the braking process and calculating the noise occurrence rate. The friction results of the brake pad are shown in Table 1:
[0072] Table 1 Brake pad performance in Examples 1 to 5 of the present application and the comparative example
[0073]
[0074] As can be seen from Table 1, the brake pads prepared in Examples 1 to 5 have an initial friction coefficient Greeningμ increased by more than 30%, a friction coefficient in the Burnish running-in stage increased by 18%, and a noise occurrence rate of more than 70 decibels decreased from 5.3% to less than 3%. It can be seen that after the coating is applied to the surface of the brake pad, the initial friction coefficient is greatly improved, and the noise occurrence rate is reduced.
[0075] The coating material provided by the present invention uses potassium titanate and aluminum oxide as main raw materials. Potassium titanate has good wear resistance and high temperature resistance, can effectively extend the service life of the brake pad, and can still maintain stable performance at high temperature. Aluminum oxide not only has good wear resistance, but also can improve the surface smoothness of the brake pad, reduce braking noise, and improve driving comfort. Calcium titanate and iron powder can both increase the friction coefficient of the brake pad. Furthermore, the coating material is coated on the friction block in a Koch snowflake pattern, which can effectively save the use of coating materials, and the Koch snowflake pattern tends to an infinite circumference, which can effectively dissipate the heat generated by the contact friction between the coating material and the brake disc, avoiding the generation of local heat accumulation areas on the friction surface and affecting the stability of the braking performance. Therefore, the present invention effectively overcomes some practical problems in the prior art and has a high utilization value and use significance.
[0076] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A coating material, characterized in that: Calculated by mass percentage, the coating material includes the following components: 40-70% potassium titanate and aluminum oxide, 10-25% calcium carbonate, 1-5% sodium silicate, 8-20% iron powder, and 8-12% liquid phenolic resin, wherein the mass ratio of the potassium titanate to the aluminum oxide is (25-40):(15-30).
2. The coating material according to claim 1, characterized in that The gel time of the liquid phenolic resin is 120-180s / 150°C.
3. The coating material according to claim 1, characterized in that The particle size of the potassium titanate is 20 to 50 μm.
4. The coating material according to claim 1, characterized in that The particle size of the aluminum oxide is 3 to 7 μm.
5. A method for preparing the coating material according to any one of claims 1 to 4, characterized in that: The steps include: Adding potassium titanate, aluminum oxide, calcium carbonate, sodium silicate and iron powder into liquid phenolic resin; In a vacuum mixer, the mixture is first stirred at a speed of 80 to 150 r / min for 3 to 5 min, and then stirred at a speed of 200 to 300 r / min for 3 to 5 min to obtain a coating material.
6. A brake pad, characterized in that: The invention comprises a steel back, a friction block and a coating made of the coating material according to any one of claims 1 to 4, wherein the coating is coated on the surface of the friction block.
7. The brake pad according to claim 6, characterized in that: The coating area of the coating is 50-70% of the area of the friction block.
8. The brake pad according to claim 6, characterized in that: The pattern of the coating is a Koch snowflake pattern.
9. The brake pad according to claim 6, characterized in that: The preparation of the coating comprises the following steps: Applying the coating material to the surface of the friction block; The coating material is cured at 150° C. for 120 to 180 seconds to form the coating.
10. The brake pad according to claim 6, characterized in that: The coating thickness of the coating material is 0.1 to 0.3 mm.